2022
DOI: 10.1136/bmjopen-2021-054142
|View full text |Cite
|
Sign up to set email alerts
|

Primary care doctor and nurse consultations among people who live in slums: a retrospective, cross-sectional survey in four countries

Abstract: ObjectivesTo survey on the availability and use of primary care services in slum populations.DesignRetrospective, cross-sectional, household, individual and healthcare provider surveys.SettingSeven slum sites in four countries (Nigeria, Kenya, Pakistan and Bangladesh).ParticipantsResidents of slums and informal settlements.Primary and secondary outcome measuresPrimary care consultation rates by type of provider and facility.ResultsWe completed 7692 household, 7451 individual adult and 2633 individual child sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…We report strong positive correlations in S3 Text. In our previous research [5], we find that there is a significantly longer average time to visit hospitals as opposed to clinics, which we also observe here. Several other studies looking into health-seeking behaviour also make this assumption [11,13,14].…”
Section: Limitationssupporting
confidence: 87%
See 3 more Smart Citations
“…We report strong positive correlations in S3 Text. In our previous research [5], we find that there is a significantly longer average time to visit hospitals as opposed to clinics, which we also observe here. Several other studies looking into health-seeking behaviour also make this assumption [11,13,14].…”
Section: Limitationssupporting
confidence: 87%
“…Surveys were conducted for each slum in the form of a questionnaire on an individual and HCP level. In the case of individuals, the survey comprised 506 questions and focused on the respondents' socioeconomic circumstances, as well as their relationship to, and interactions with, HCPs-described in detail elsewhere [5,21]. The individual-level survey was conducted on thousands of individuals for each slum, as detailed in Table 1.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study by Buigut et al [54] in the study area showed that seeking care in a public health facility was associated with increased odds of experiencing catastrophic health expenditure and for this reason many informal slum residents would forgo health service utilization. A more recent collaborative study looking to improve slum health in the study area also found that many households in the study area spent a significant proportion of their money on healthcare [55].…”
Section: Discussionmentioning
confidence: 76%